Five-Strand versus Four-Strand Hamstring Tendon Graft Technique for Anterior Cruciate Ligament Reconstruction: A Biomechanical Comparison - Vaillant, Eric R.; Parks, Brent G.; Camire, Lyn M.; Hinton, Richard Y. (The Journal of Knee Surgery, 2017)
The aim of this article is to compare diameter and stiffness, displacement, and strain in a five-strand versus four-strand hamstring graft for anterior cruciate ligament reconstruction. Eight matched pairs of lower extremities underwent four-strand or five-strand hamstring graft reconstruction. Diameter was significantly higher in the five-strand versus the four-strand construct (p = 0.002). No significant difference was found between the groups in construct displacement or stiffness. Significantly higher strain was observed in the inner limb versus the outer limb in the four-strand construct (p = 0.001) and in the inner limb versus the fifth limb in the 5-strand construct (p = 0.004). A fifth limb added to a four-strand hamstring graft significantly increased graft diameter but did not significantly change stiffness or displacement, suggesting that attachment of additional graft material via suture did not provide for full incorporation of the added limb into the graft at time zero. The inner limb in both constructs absorbed significantly greater load than did other limbs. The use of suture to attach additional material to a four-strand hamstring graft may not contribute to improved biomechanical qualities of the graft at time zero.
Keywords: hamstring graft; anterior cruciate ligament; reconstruction; cortical button